Indole and azaindole halogenation catalyzed by the RebH enzyme variant 3-LSR utilizing co-purified E. coli reductase - Li, Eunice Hui Yen; Sana, Barindra; Ho, Timothy; Ke, Ding; Ghadessy, Farid J.; Duong, Hung A.; Seayad, Jayasree (Frontiers in Bioengineering and Biotechnology, 2022)
Biocatalytic C-H halogenation is becoming increasingly attractive due to excellent catalyst-controlled selectivity and environmentally benign reaction conditions. Significant efforts have been made on enzymatic halogenation of industrial arenes in a cost-effective manner. Here we report an unprecedented enzymatic halogenation of a panel of industrially important indole, azaindole and anthranilamide derivatives using a thermostable RebH variant without addition of any external flavin reductase enzyme. The reactions were catalyzed by the RebH variant 3-LSR enzyme with the help of a co-purified E. coli reductase identified as alkyl hydroperoxide reductase F (AhpF).